Factores que inciden en el desarrollo de los fundamentos técnicos del voleibol para fomentar este deporte en los centros educativos - Quezada Honores, Wilmer Bolívar (My University, 2021)
Volleyball is a sport that requires speed and speed in the play. In this sport the technical fundamentals predominate that are necessary to know and apply them during the match. The technical foundations of volleyball are the appropriate knowledge that the players have in performing the movements of displacement, for the serve, the attack, blocking and defense during the game, putting dynamism in sports competition. In the development of these fundamentals, psychological, physical and technical factors affect the performance of a good play. In carrying out this essay, the general objective was: To establish the factors that influence the development of the technical foundations of volleyball to promote this sport in educational centers. As specific objectives: Analyze what are the factors that incur in the development of the technical foundations of volleyball. Determine the importance of mastering the technical fundamentals and tactics of volleyball. To meet the stated objectives, a bibliographic research was carried out to search for information in scientific sources that support the theoretical foundation of the technical foundations of volleyball and the factors that affect them. Among the psychological factors, thought, language, perception, precision and memory predominate. Among physicists, speed and flexibility; and among the technicians is the movement, posture and ways of hitting. The analysis of these factors allows us to know which aspects have a favorable impact on the game of volleyball; as well as, what plays or mistakes should not be made again. Therefore, it is essential that teachers know these fundamentals and the factors that affect their application so that they can apply them with students.
El voleibol es una disciplina deportiva que necesita de rapidez y velocidad en la jugada. En este deporte predominan los fundamentos técnicos que son necesarios conocerlos y aplicarlos durante el partido. Estos no son otra cosa que los conocimientos apropiados que poseen los jugadores en realizar los movimientos de desplazamiento, para el saque, ataque, bloqueo y defensa durante el juego poniendo el dinamismo en la competencia deportiva. En el desarrollo de estos fundamentos inciden factores psicológicos, físicos y técnicos que contribuyen a la realización de una buena jugada. En la realización del presente ensayo se planteó como objetivo general: Establecer los factores que inciden en el desarrollo de los fundamentos técnicos del voleibol para fomentar este deporte en los centros educativos. Como objetivos específicos: Analizar cuáles son los factores que incurren en el desarrollo de los fundamentos técnicos del voleibol. Determinar la importancia del dominio de los fundamentos técnicos y las tácticas del voleibol. Para cumplir con los objetivos planteados, se realizó una investigación bibliográfica seleccionando fuentes científicas que sustentan la fundamentación teórica de los fundamentos técnicos del voleibol y los factores que inciden en ellos. Entre los factores psicológicos predominan el pensamiento, lenguaje, percepción, precisión y memoria. Entre los físicos la velocidad y flexibilidad; y, entre los técnicos está el desplazamiento, postura y formas de golpeo. El análisis de estos factores permite conocer que aspectos inciden favorablemente en el juego del voleibol; así como también, que jugadas o equivocaciones no se debe cometer otra vez.
Keywords: FUNDAMENTO; TECNICO; VOLEIBOL; FACTOR PSICOLOGICO